Sprayable tissue adhesive with biodegradation tuned for prevention of postoperative abdominal adhesions. Issue 1 (23rd May 2022) - Erdi, Metecan; Rozyyev, Selim; Balabhadrapatruni, Manogna; Saruwatari, Michele S.; Daristotle, John L.; Ayyub, Omar B.; Sandler, Anthony D.; Kofinas, Peter
Abstract: Adhesions are dense, fibrous bridges that adjoin tissue surfaces due to uncontrolled inflammation following postoperative mesothelial injury. A widely used adhesion barrier material in Seprafilm often fails to prevent transverse scar tissue deposition because of its poor mechanical properties, rapid degradation profile, and difficulty in precise application. Solution blow spinning (SBS), a polymer fiber deposition technique, allows for the placement of in situ tissue‐conforming and tissue‐adherent scaffolds with exceptional mechanical properties. While biodegradable polymers such as poly(lactic‐co‐glycolic acid) (PLGA) have desirable strength, they exhibit bulk biodegradation rates and inflammatory profiles that limit their use as adhesion barriers and result in poor tissue adhesion. Here, viscoelastic poly(lactide‐co‐caprolactone) (PLCL) is used for its pertinent biodegradation mechanism. Because it degrades via surface erosion, spray deposited PLCL fibers can dissolve new connections formed by inflamed tissue, allowing them to function as an effective, durable, and easy‐to‐apply adhesion barrier. Degradation kinetics are tuned to match adhesion formation through the design of PLCL blends comprised of highly adhesive "low"‐molecular weight (LMW) constituents in a mechanically robust "high"‐molecular weight (HMW) matrix. In vitro studies demonstrate that blending LMW PLCL (30% w/v) with HMW PLCL (70% w/v) yields an anti‐fibrotic yet tissue‐adhesive polymer sealant with a 14‐day erosion rate countering adhesion formation. PLCL blends additionally exhibit improved wet tissue adhesion strength (~10 kPa) over a 14‐day period versus previously explored biodegradable polymer compositions, such as PLGA. In a mouse cecal ligation model, select PLCL blends significantly reduce abdominal adhesions severity versus no treatment and Seprafilm‐treated controls.